2022
DOI: 10.1002/pro.4333
|View full text |Cite
|
Sign up to set email alerts
|

Complementing machine learning‐based structure predictions with native mass spectrometry

Abstract: The advent of machine learning-based structure prediction algorithms such as AlphaFold2 (AF2) and RoseTTa Fold have moved the generation of accurate structural models for the entire cellular protein machinery into the reach of the scientific community. However, structure predictions of protein complexes are based on user-provided input and may require experimental validation. Mass spectrometry (MS) is a versatile, time-effective tool that provides information on post-translational modifications, ligand interac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…show that the CCS of the heterocomplex is closer to the AF2 rank 1 structure with A bound inside the TTR tetramer, rather than the AF2 rank 3 structure with A bound on the surface of TTR. The ATD of apo-TTR is shown in grey, that of the TTR-A (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) complex in blue. (G) Further evidence for binding in the central channel is given by the minimal A binding to TTR after overnight incubation, when the tetramer is stabilized by co-incubation with tafimidis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…show that the CCS of the heterocomplex is closer to the AF2 rank 1 structure with A bound inside the TTR tetramer, rather than the AF2 rank 3 structure with A bound on the surface of TTR. The ATD of apo-TTR is shown in grey, that of the TTR-A (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) complex in blue. (G) Further evidence for binding in the central channel is given by the minimal A binding to TTR after overnight incubation, when the tetramer is stabilized by co-incubation with tafimidis.…”
Section: Discussionmentioning
confidence: 99%
“…We next performed native MS to experimentally test these predictions. Weak binding of A (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) to TTR at a 1:4 stoichiometry was observed, with the intensity of the peaks increasing upon overnight incubation at room temperature (Figure 2C-D). Complex formation was confirmed using MS/MS (Figure 2E).…”
Section: Binding Of Monomeric A To Ttr and T80 Requires Exposed Subu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Mass spectrometry (MS) is another experimental approach which well complements structure prediction methods. Indeed, several studies have shown how MS data can be combined with AF2 models. Specific tools have been developed to include MS data in the modeling process, namely, AlphaLink and its extension to AlphaFold-Multimer, AlphaLink2 …”
Section: Integrating Af2 Into Experimental Pipelinesmentioning
confidence: 99%